Small molecule grp94 inhibitors block dengue and Zika virus replication - Rothan, Hussin A.; Zhong, Yongwang; Sanborn, Mark A.; Teoh, Teow Chong; Ruan, Jingjing; Yusof, Rohana; Hang, Jun; Henderson, Mark J.; Fang, Shengyun (Elsevier Masson, 2019)
Two major flaviviruses, dengue virus (DENV) and Zika virus (ZIKV), cause severe health and economic burdens worldwide. Recently, genome-wide screenings have uncovered the importance of regulators of the Hrd1 ubiquitin ligase-mediated endoplasmic reticulum (ER)-associated degradation (ERAD) pathway for flavivirus replication in host cells. Here we report the identification of the compound Bardoxolone methyl (CDDO-me) as a potent inhibitor of the Hrd1 ubiquitin ligase-mediated ERAD, which possesses a broad-spectrum activity against both DENV and ZIKV. Cellular thermal shift assay (CETSA) suggested that CDDO-me binds to grp94, a key component of the Hrd1 pathway, at a low nanomolar concentration, whereas interaction was not detected with its paralog Hsp90. CDDO-me and the grp94 inhibitor PU-WS13 substantially suppressed DENV2 replication and the cytopathic effects caused by DENV and ZIKV infection. The antiviral activities of both compounds were demonstrated for all four DENV serotypes and four ZIKV strains in multiple human cell lines. This study defines grp94 as a crucial host factor for flavivirus replication and identified CDDO-me as a potent small molecule inhibitor of flavivirus infection. Inhibition of grp94 may contribute to the antiviral activity of CDDO-me. Further investigation of grp94 inhibitors may lead to a new class of broad-spectrum anti-flaviviral medications. © 2019 Elsevier B.V.